Qualidade de vida de mulheres portadoras de câncer de mama integrantes da associação Amigas do Peito de Bauru - Landro, Izabel Cristina Rossi (2010)
Breast cancer is a worldwide concern. The survival rate of women treated for breast cancer has been increasing with the effectiveness of treatment and particularly with early diagnosis. This study aims to highlight the importance of the medical choice on the type of surgery and breast reconstruction when necessary to guarantee the quality of life of these women, reducing the consequences of this illness on its victims. In this work, through the use of the SF-36, 50 women who have had breast cancer with an average age of 57.2 years were interviewed to evaluate their quality of life, observing the difference between groups of mastectomy women with and without breast reconstruction and groups of women who submitted to quadrantectomy that did not need reconstruction or did not undertake reconstruction, coming to the identification of the mastectomy women group with breast reconstruction and the group that did not need reconstruction had better scores in different areas such physical functioning, pain, social functioning, vitality and mental health.